Identification of Ethanol and 4‐Nitroquinoline‐1‐Oxide Induced Epigenetic and Oxidative Stress Markers During Oral Cavity Carcinogenesis. (24th July 2015) - Urvalek, Alison M.; Osei‐Sarfo, Kwame; Tang, Xiao‐Han; Zhang, Tuo; Scognamiglio, Theresa; Gudas, Lorraine J.
<x xml:space="preserve">Abstract</x> Background Head and neck squamous cell carcinoma (HNSCC) is a cancer that is characterized by its high morbidity and mortality rates. While tobacco use and alcohol consumption are 2 major contributing factors for HNSCC carcinogenesis, how the combination of tobacco and alcohol increases HNSCC risk is not understood. Methods We combined the 4‐nitroquinoline‐1‐oxide (4‐NQO) oral carcinogenesis and Meadows–Cook alcohol mouse models to elucidate the molecular events and to identify the novel biomarkers associated with oral cancer development. Results By genome‐wide RNA‐seq of tongue samples (3 mice per group), we identified changes in transcripts that mediate alcohol metabolism and oxidative stress (Aldh2, Aldh1a3, Adh1, Adh7, and Cyp2a5) in mice treated with 4‐NQO followed by ethanol (4‐NQO/EtOH) as compared to the vehicle control/untreated (V.C./Untr.) samples. We measured major, global increases in specific histone acetylation and methylation epigenetic marks (H3K27ac, H3K9/14ac, H3K27me3, and H3K9me3) in the oral cavities of V.C./EtOH, 4‐NQO/Untr., and 4‐NQO/EtOH treatment groups compared to the V.C./Untr. group. We detected changes in histone epigenetic marks near regulatory regions of genes involved in ethanol metabolism by chromatin immunoprecipitation. For instance, the Aldh2 promoter showed increased H3K27me3 marks, and Aldh2 mRNA levels were reduced by 10‐fold in 4NQO/EtOH versus V.C./Untr. tongue samples. 4‐NQO/EtOH treatment also caused increases in markers of oxidative stress, including 4‐HNE, MCT4/SLC16a3, and TOM20, as measured by immunohistochemistry. Conclusions We delineate a mechanism by which 4‐NQO and ethanol can regulate gene expression during the development of HNSCC and suggest that histone epigenetic marks and oxidative stress markers could be the novel biomarkers and targets for the prevention of HNSCC.